INTERPERSONAL COMMUNICATION IN THE RECOVERY EFFORTS OF MENTALLY ILL STUDENTS AT THE BOARDING SCHOOL CONDROMOWO 2 NGAWI DISTRICT - Sholihah, Anisa Nuraini Maratu; Iswahyudi, Iswahyudi (UIN Kiai Ageng Muhammad Besari Ponorogo, 2023)
The purpose of this article is to find out the form of interpersonal communication in the recovery efforts of mentally ill students at Condromowo 2 Islamic Boarding School and the supporting and inhibiting factors in the recovery process of mentally ill students. The method used in this article is descriptive qualitative method with data collection through interviews, observation, documentation, and literature research. The results of this analysis show that there are five forms of interpersonal communication in the recovery efforts of mentally ill students, namely dialogue, sharing, interviews, counseling, and spiritual therapy. In the process of dialoguing with students, there is one-way communication, two-way communication, the use of verbal language, and the use of non-verbal language. Sharing occurs when students already have trust in the rehabilitation sector administrators. The interview occurs when the santri are not clear about their problems, thus encouraging the administrators to ask deeper questions. Counseling is done by providing solutions to the problems experienced by students. As for spiritual therapy using alternative wirid, reciting the Koran, reading sholawat, and praying in congregation five times. The supporting factors contained in the interpersonal communication process between rehabilitation administrators and mentally ill students can be divided into three, namely supporting factors from the communicator's angle, supporting factors from the communicator's angle, and supporting factors from the message angle. The obstacles that occur during the recovery process of mentally ill students are process, semantic, and psychological obstacles.